2020
DOI: 10.1108/jhr-02-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' knowledge and attitudes regarding brominated flame retardants from three Croatian universities

Abstract: PurposeThis study explored Croatian nursing students' knowledge and attitudes regarding brominated flame retardants (BFRs) as indicators of their predisposition to educate future patients. The purpose of the study was to identify knowledge gaps and barriers and to propose possible remedies.Design/methodology/approachThe cross-sectional survey was conducted on a convenience sample of 114 nursing students at undergraduate and graduate levels from three Croatian universities during the winter semester in the acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The Sustainable Development Goals (SDG) elements: good health and well-being, clean water and sanitation, and climate actions are interconnected and imperative triangles for reducing neonatal and childhood mortality (9). Globally, the environment contributes to about 13.7 million (24%) deaths, including one in four deaths of children under five years of age and more than a quarter (23%) of disease burdens (10). The World Health Organization (WHO) reported that 1.8 billion (93%) children under 15 breathe polluted air, putting their health and development at serious risk (11).…”
Section: Introductionmentioning
confidence: 99%
“…The Sustainable Development Goals (SDG) elements: good health and well-being, clean water and sanitation, and climate actions are interconnected and imperative triangles for reducing neonatal and childhood mortality (9). Globally, the environment contributes to about 13.7 million (24%) deaths, including one in four deaths of children under five years of age and more than a quarter (23%) of disease burdens (10). The World Health Organization (WHO) reported that 1.8 billion (93%) children under 15 breathe polluted air, putting their health and development at serious risk (11).…”
Section: Introductionmentioning
confidence: 99%